Measuring supply chain complexity based on multi-criteria decision approach - Piya, S.; Khadem, M.; Al Kindi, M.; Shamsuzzoha, A. (IEOM Society, 2020)
This study identified twenty-two drivers that cause the complexity in supply chain. The level of such complexity is quantified by using hybrid AHP and GRA method. A case company is studied in order to demonstrate the applicability of the proposed method. The results from the case company were analyzed and it is seen that the level of supply chain complexity of the case company is 0.44, which is signifying that there is a considerable scope of improvement in terms of minimizing complexity in its supply chain. From the study outcomes, it is realized that the case company mainly needs substantial improvement on the issues of “government regulation,” “internal communication and information sharing,” and “company culture” in order to minimize the level of accompanied complexity in its supply chain.
Keywords: Analytical hierarchy process; case study; Complexity measurement; Grey relational analysis; Supply chain complexity; fi=Tuotantotalous|en=Industrial Management|